Fatwa on the Islamic Law Transaction and Its Role in the Islamic Finance Ecosystem - Fakhrunnas, Faaza (Al Tijarah, 2018)
Fatwa holds a pivotal role in determining the guidance of Islamic society especially in Islamic finance ecosystem. Moreover, fatwa will render the direction for Islamic finance and then it will impact to the stakeholders of Islamic finance ecosystem such as regulator, Islamic finance institution, investor, and the market performance. This paper will discuss about the role of fatwa on the Islamic law transaction and its effect to Islamic finance performance. By adopting content analysis as the method of the study, this paper finds that firstly there has several fatwa having any dispute among the Islamic scholars and Islamic fatwa institution such as sukuk nature, bay al-inah, the nature of interest, bay al-dayn, and screening methodology adopted by several indices. Secondly, the different fatwa issued by Islamic scholars and Islamic fatwa institution influence the performance of Islamic finance product in the market which affect the stakeholders of Islamic finance industry.